In a fix: Africa's place in the Belt and Road Initiative and the reproduction of dependency. Issue 3 (2nd July 2020) - Taylor, Ian; Zajontz, Tim
ABSTRACT: The Belt and Road Initiative (BRI) aims to integrate Africa into an ambitious Chinese-constructed infrastructure network. The terms of this integration however deepen Africa's dependent position and perpetuate its terms of (mal)integration into the global political economy. These terms, which are characterised by external domination and socially-injurious and extraverted modes of accumulation, are likely to be exacerbated by the BRI's focus on facilitating extraction from the African continent while importing huge amounts from China. While the BRI aims to resolve contradictions within China's own economy, the latent dynamics within the BRI vision may result in an entrenched African dependency.